9th International Bielefeld Conference 2009: Upgrading the eLibrary: Enhanced Information Services Driven by Technology and Economics - Gastinger, Almuth (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2009)
Thisarticle reports on the 9th International Bielefeld Conference ‘Upgrading the eLibrary: Enhanced Information Services Driven by Technology and Economics’, 3-5 February 2009, in Bielefeld, Germany. The conference focused on future challenges for libraries regarding the development of information services and infrastructures that meet the changing needs of scholarly communication, collaboration (e-science) and publication (open access) as well as new requirements regarding teaching and learning (virtual learning spaces). In addition attention was paid to economic conditions and strategic positioning of libraries as a general framework for information services.